THE EFFECTIVENESS OF LEADERSHIP STYLE TO THE EMPLOYEE PERFORMANCE (THE STUDY ON EMPLOYEES IN ENGLISH LANGUAGE EDUCATION DEPARTMENT) - Batubara, M. Daud; Kasman, Kasman; Cabiles, Roldan Caparino (Dinasti Publisher, 2020)
This study aims to determine the effectiveness of leadership style to employee performance (study on English language education department). This study was quantitative research. The data of collecting used questioner. The population is seventeen and as sample. The analysis data of technique descriptive analysis and Likert scale. The result of this study shown that The four variables (leadership style) have an important influence to Y (employee performance). This can be seen from sales above almost all respondents answer strongly agree of category. This means that leadership style has big influence to employee performance in English Education Language Department, State of Islamic (STAIN) Mandaling Natal.